Medium term socio-economic policy framework 2015-2018 : achieving inclusive growth and sustainable development - final draft (2015)
Speaks to the four medium term themes viz., development and protection of human capital; national security and justice; economic stability, growth and employment; and environmental sustainability and climate change response which are geared towards moving Jamaica towards its goal of achieving inclusive growth and sustainable development.
Keywords: DEVELOPMENT PLANS